Prevalence of selected intestinal protozoan infections in marginalized rural communities in Palestine - Amer Al-Jawabreh; Suheir Ereqat; Kamal Dumaidi; Hanan Al-Jawabreh; Ziad Abdeen; Abdelmajeed Nasereddin (BMC, 2019)
Abstract Background Intestinal parasitic infections are common in rural areas with poor infrastructure and low socioeconomic status. The aim of this study was to estimate the prevalence of selected parasitic infections in marginalized rural areas in the northern part of the Palestinian West Bank Region, using conventional and PCR-based methods, and also to assess risk predictors of infection. Methods A cross-sectional study was conducted on 104 individuals from three rural villages in the Jordan Valley. Stool samples were collected and examined by a battery of tests that included microscopy of wet fecal samples in normal saline with iodine, concentration by ethyl acetate sedimentation and also by zinc sulfate floatation, a conventional PCR and a real-time PCR (qPCR). Risk factors were assessed that included demographic, socioeconomic, and behavioral characteristics. Data on method performance was analyzed by kappa-statistic, Cochrane's Q, and McNemar post hoc test. Mid-P exact test and odds ratio were used to discern association between outcome and risk predictors. Results The overall prevalence of intestinal parasitic infections was 48% (49/102). The predominant parasites were Giardia lamblia at 37% (37/102) and Hymenolepis nana at 9% (9/102). To concentrate cysts and eggs, sedimentation can be used as an alternative to floatation with a loss of 1% of positive cases. The methods employing PCRs proved crucial as it increased the detected infection rate of G. lamblia approximately three-fold from 13% by the conventional methods to 37% by the qPCR. Multiple infections were present in 13% (13/102) of the study group, which included double (10%) and triple (3%) infections. Regarding the genus Entamoeba, E. dispar and E. coli were detected at rates of 2 and 8%, respectively. While none of the individuals were infected with the pathogenic E. histolytica, E. nana (4%) was detected for the first time in the area. Age was a risk predictor for infection (OR = 2.61, CI 95% 1.05-6.45, P = 0.038). Conclusions The increased prevalence of intestinal parasitic infections in children in marginalized rural areas in Palestine is worrying. The addition of PCR-based methods is important for the diagnosis of such infections as, with cautious interpretation, it increases proficiency and overcomes underestimation and misdiagnosis of cases. Control measures including education on personal hygiene and environmental sanitation, should be introduced to reduce the prevalence of the intestinal parasites and, thus, the infections they cause in this and other areas.